2021
DOI: 10.1007/s11906-021-01159-0
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Trends in Hypertension Prevalence, Awareness, Treatment, and Control Rate in the Middle East and North Africa: a Systematic Review and Meta-analysis of 178 Population-Based Studies

Abstract: Purpose of ReviewThis study investigated and pooled the long-term trends in prevalence, awareness, treatment, and control of hypertension (HTN) in the Middle East and North Africa (MENA) region. In this systematic review and meta-analysis, we searched MEDLINE/PubMed, Web of Science, Google Scholar, EMBASE, and Scopus between database inception and November 2020. All cross-sectional studies that investigated the prevalence of pre-HTN, HTN, awareness, treatment, and control in the MENA counties were included. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 93 publications
2
11
0
Order By: Relevance
“…For controlled HTN, treatment adherence is crucial. In this aspect, factors like education level and social support play an essential role, similar to those observed in other countries (4143) . The difficulty in controlling HTN despite treatment may be related to genetic factors, lifestyle, and the presence of concomitant diseases.…”
Section: Discussionsupporting
confidence: 69%
“…For controlled HTN, treatment adherence is crucial. In this aspect, factors like education level and social support play an essential role, similar to those observed in other countries (4143) . The difficulty in controlling HTN despite treatment may be related to genetic factors, lifestyle, and the presence of concomitant diseases.…”
Section: Discussionsupporting
confidence: 69%
“…Hence, early initiation of pharmacologic therapy as indicated, single-pill regimens, and telehealth programs should be considered in these individuals to improve drug adherence and BP control [ 29 30 ]. A recent systematic review and meta-analysis pooling evidence from 107 national and subnational studies in Iran showed that the BP control rate varies from 4.5% to 68.39% between different geographical regions [ 31 ]. This highlights the importance of our region-specific findings among adult residents of Tehran, which is one of the largest metropolitan areas in the Middle East.…”
Section: Discussionmentioning
confidence: 99%
“…The disparities in response distribution in our study, on the other hand, could point to a general distribution per category that is independent of the pandemic. For example, the fact that more men reported high blood pressure and smoking while more women reported low physical activity may reflect the well-known high prevalence of hypertension and smoking in men while women are more sedentary ( 40 , 41 ).…”
Section: Discussionmentioning
confidence: 99%